(untitled) (Academicia Globe: Inderscience Research, 2023)
In reaserch, this was studied on experimental wounds by coating the skin and subcutaneous structures with gauze impregnated with a sericin-preserving mixture for regenerative processes, during which it was found that the acceleration of regenerative processes occurs on average 5-7 days earlier than in the control group, there are no rough scars on the wounds. This gauze bandage, which has absorbed the sericin-containing composition, creates and maintains a moist environment in the wound for up to 3-4 days. It actively promotes the painless removal of necrosis and fibrin, absorbs ulcer exudate for a long time, accelerates its purification, reduces the influence of infectious factors. This will prevent the wound exudate from sticking. They allow you to control the wound process.